Development of Interactive Mathematics E-Modules to Improve Elementary School Students' Learning Outcomes and Critical Thinking Skills - Sofiah, Nur; Wiryanto, Wiryanto; Mariana, Neni (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
The study's background stems from the low mathematics learning outcomes and critical thinking skills of students, which are a result of limited supporting learning media. Therefore, this study intends to develop an interactive mathematics e-module aimed at improving learning outcomes and critical thinking skills of fifth-grade elementary school students on spatial geometry material. The research method used is the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. We conducted this research in class V of Kyai Ibrahim Elementary School. The results of the study indicate that the interactive e-module developed is very feasible, with media expert validation of 95.3%, material expert validation of 91.7%, and learning device expert validation of 89%. The practicality of this e-module is supported by the results of teacher responses of 96% and student responses of 93%, which are categorized as very practical. The product's effectiveness is shown by the fact that 89% of students completed their learning in large classes during the implementation stage, and there was an improvement in learning results and critical thinking skills, with an N-Gain value of 0.72 (72.09%). Student activity during implementation also increased, with 89% categorized as very active. Thus, this interactive e-module has proven effective in improving learning outcomes and critical thinking skills among fifth-grade elementary school students.